2006
DOI: 10.1007/s11886-006-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone: A multifaceted antiarrhythmic drug

Abstract: Synthesized as an antianginal compound 40 years ago, amiodarone has emerged as a uniquely effective antiarrhythmic compound in recent years. It has numerous properties, the most prominent being the ability to lengthen repolarization in the atria and ventricles associated with bradycardia without the significant potential for torsades de pointes. Amiodarone effectively controls a wide spectrum of atrial and ventricular antiarrhythmic disorders, but its limiting side effects, such as thyroid dysfunction, pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…The fact that this drug exhibits the added benefit of reducing the parasite burden and at the same time operates synergistically, enhancing the efficacy of other specific antiparasitic agents, highlights the multiple properties of this compound and places this agent as a first-line drug not only for the symptomatic treatment of arrhythmias but as an anti-T. cruzi drug. Nevertheless, its long-term use in some patients may be limited due to its potential side effects, such as pulmonary fibrosis, thyroid dysfunction and skin pigmentation; thus, patients must be carefully monitored [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that this drug exhibits the added benefit of reducing the parasite burden and at the same time operates synergistically, enhancing the efficacy of other specific antiparasitic agents, highlights the multiple properties of this compound and places this agent as a first-line drug not only for the symptomatic treatment of arrhythmias but as an anti-T. cruzi drug. Nevertheless, its long-term use in some patients may be limited due to its potential side effects, such as pulmonary fibrosis, thyroid dysfunction and skin pigmentation; thus, patients must be carefully monitored [23] .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that amiodarone inhibits the activity of carnitine palmitoyltransferase-1, an enzyme involved in the metabolism of fatty acids, a potentially harmful energy substrate in situations of ischemia [114]. Amiodarone was shown to prevent induction of the MPTP on heart mitochondria, while being toxic to mitochondria from other tissues [115].…”
Section: Hemodynamic Drugsmentioning
confidence: 99%
“…Amiodarone is a class III antiarrhythmic drug. It inhibits repolarizing K + currents and so prolongs the cardiac AP; it weakly inhibits depolarizing currents, such as those mediated by the Na + and Ca 2+ channels [32][33][34] . Therefore, it was worth comparing the electrophysiological effects of these two drugs.…”
Section: Discussionmentioning
confidence: 99%